(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Image compression is improved by decreasing the image before the encryption process and evaluating the missing area after decoding at lower bit rates. First the input RGB Brain MRI image is modified to gray scale Image. In our proposed approach, the input MRI image is pre-processed to reduce the image as down sampling image. Radon Transform is then applied for the image and then background is reduced by using soft threshold. Thereafter, to find the smooth threshold values of the image using genetic algorithm, then Image size is removed using Euclidean distance of similar blocks. This provides a sample output under a given input MRI image. This approach has showed good PSNR improvement compare with existing techniques. Finally this approach gives at higher bitrates.